The influence of interpersonal relationships on college students’ physical activity: chain-mediated effects of social support and exercise motivation - Yiqing Wang; Yue Wang; Moran Lv; Zhichen Cheng; YuLiu Tao (Frontiers in Psychology)
BackgroundWhile interpersonal relationships are known to benefit psychological health and personal development, their role in shaping physical activity behaviors among university students has yet to be thoroughly investigated. Gaining insight into the mechanisms linking these relationships to physical activity is crucial for developing effective strategies to encourage more active lifestyles in this demographic.ObjectiveThis study seeks to investigate how interpersonal relationships affect physical activity in university students, with a particular focus on the sequential mediating roles of social support and motivation to exercise. The findings are intended to inform theory and guide the design of practical interventions to enhance physical activity among this population.MethodsA total of 635 university students were surveyed using a random sampling approach and a set of validated instruments, including the Comprehensive Diagnostic Scale for Interpersonal Relationships, the Physical Activity Motivation Scale, the Social Support Scale for Physical Activity, and the short version of the International Physical Activity Questionnaire (IPAQ-SF). Data analysis was conducted with SPSS 27.0, employing methods such as independent sample t-tests, one-way ANOVA, Pearson correlation analysis, Harman’s single-factor test to check for common method bias, and bootstrapped mediation testing using the PROCESS macro.ResultsInterpersonal relationships were found to significantly influence university students’ physical activity, with this effect partially explained by the sequential mediation of social support and motivation to exercise. More specifically, interpersonal relationships were negatively associated with both social support and exercise motivation (β = −0.097, p = 0.014; β = −0.126, p = 0.001), whereas social support was positively associated with motivation to exercise (β = 0.316, p < 0.001). When all variables were included in the model, both social support and exercise motivation showed significant positive effects on physical activity levels (β = 0.241, p < 0.001; β = 0.127, p = 0.002). Mediation analysis further revealed a significant total indirect effect (value = −0.091) of social support and motivation to exercise on the relationship between interpersonal relationships and physical activity, with all three pathways—via social support, via motivation, and via the combined path of social support and motivation—yielding significant mediation effects.ConclusionThis study underscores the importance of interpersonal relationships, social support, and exercise motivation in shaping physical activity among university students, with particular emphasis on the interconnected mediation pathways among these factors. The results offer a theoretical basis for developing targeted physical activity interventions, highlighting the need to address these elements collectively rather than in isolation. Future studies are encouraged to explore how these relationships hold across diverse populations and cultural settings and to use longitudinal methods to establish causal links better.